Capital market and the determinants of development in the Republic of Macedonia - Djambaska, Elizabeta; Petkovski, Vladimir; Lozanoska, Aleksandra (Economic Development, Journal of the Institute of Economics – Skopje, 2017)
This paper considers the capital market in the Republic of Macedonia. The analysis identifies and explains whether capital market development is influenced by economic growth. The focus of the paper is to determine the effects of different factors on the capital market development in the Republic of Macedonia. For these purpose a multivariate linear regression is conducted using the data from 1997-2013. The analysis indicates that the capital market in the Republic of Macedonia is small and underdeveloped. Therefore the economic growth factors taken into consideration for the research have not shown considerable impact on the capital market due to its underdevelopment.
Keywords: Capital Market, Market Capitalization, Calderon-Rossell model, regression, Republic of Macedonia